Effectiveness of Regional Expenditure Budget Management in Riau Province: Analysis and Recommendations - Maryanti, Sri; Harahap, Toharuddin; Murni, Yanti (ADPEBI International Journal of Business and Social Science, 2025)
Objectives- The focus of this research is to offer a significant contribution in understanding the management of the Regional Expenditure Budget (APBD) in Riau Province. The data used in this study are secondary data from 2019 – 2023. By providing in-depth analysis and practical recommendations, this research can serve as a reference for policymakers and other stakeholders in formulating more effective strategies in regional financial management. Methodology- The research using quantitative analysis using research variables is divided into two, namely the main variables of APBD effectiveness, regional revenue and development investment with indicators of effectiveness ratio, income realization ratio and capital expenditure ratio and socio-economic impact variables with indicators of GDP per capita, poverty rate and open unemployment rate. Findings- This study reveals that during the period 2019 to 2023, the effectiveness of the Riau Provincial Budget fluctuated. The highest increase occurred in 2021, but in 2023 there was a slight decrease compared to the previous year. This shows that despite efforts to improve, consistency in the effectiveness of APBD management still needs to be improved through Optimizing Capital Expenditure Allocation, Improving the Quality of Budget Planning and Implementation, Strengthening Human Resources (HR) Capacity and Transparency and Accountability